Interactive Multimedia Development Based on Adobe Flash CS6 Profesional on Learning of Chemical Equilibrium - Yeni R. Saselah; Muhammad Amir M; Riskan Qadar (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2017)
The aims of this study were to produce an interactive multimedia based on Adobe Flash Cs6 Professional in one vocational school (SMK) and to know the students' response to the use of the media used. The subject of this study was 34 students in Samarinda. This study is a research development. The data were gained from a questionnaire by expert validity and response by students. The result was an interactive multimedia that could be operated in computer and Android-based handphone. Students' response to interactive multimedia in the topic chemical equilibrium used was 97,8 % positive. The conclusions were multimedia resulted are eligible to be applied in learning of chemical equilibrium in vocational school dan had a positive response from the students.